Lok Sabha elections 1989 : Indian politics in 1990's - Singh, Mahendra Prasad, 1943- (Delhi : Kalinga Publications, 1992)
Contributed articles.
Includes index.
Includes bibliographical references.
Keywords: India. -- Parliament. -- Lok Sabha -- Elections; Elections -- India